Late initiation of antenatal care visit amid implementation of new antenatal care model in Sub-Saharan African countries: A multilevel analysis of multination population survey data - Kusse Urmale Mare; Gashaye Gobena Andargie; Abdulkerim Hassen Moloro; Ahmed Adem Mohammed; Osman Ahmed Mohammed; Beriso Furo Wengoro; Begetayinoral Kussia Lahole; Tesfahun Simon Hadaro; Simeon Meskele Leyto; Petros Orkaido Mamo; Abdulhakim Hora Hedato; Beminate Lemma Seifu; et al. (PLoS ONE, 2025)
Introduction Although late initiation of antenatal care has been linked with adverse pregnancy outcomes, a significant number of pregnant women in resource-limited regions are seeking this care late. There has been a lack of information on the extent and factors influencing late initiation of antenatal care in the African context following the implementation of the new antenatal care model in 2016. Thus, we aimed to determine the pooled prevalence of late antenatal care visit and its determinants among women in Sub-Saharan Africa (SSA) using national surveys conducted after the implementation of new guidelines. Methods We analyzed data from the recent demographic and health survey (DHS) conducted in 16 SSA between 2018 and 2022 using a weighted sample of 101,983 women who had antenatal care follow-up during their index pregnancy. A multilevel logistic regression models were fitted and likelihood and deviance values were used for model selection. In the regression model, we used adjusted odds ratios along with their corresponding 95% confidence intervals to determine the factors associated with late antenatal care visit. Results The pooled prevalence of late antenatal care visit among pregnant women in SSA was 53.8% [95% CI: 46.2% - 61.3%], ranging from 27.8% in Liberia to 75.8% in Nigeria. Women’s age and education, working status, partner’s education, health insurance coverage, birth order, household wealth, age at marriage, decision on health care, residence, and community-level women’s illiteracy were the factors associated with late antenatal care visit. Conclusion More than half of pregnant women in SSA initiated attending antenatal care during late pregnancy, with significant differences seen among countries. These results underscore the necessity for focused interventions to tackle these issues and enhance prompt access to antenatal services for better maternal and child health outcomes in the area. Moreover, creating tailored interventions for younger women, those with multiple previous births, employed women, and those who experienced early marriage to address their specific challenges and obstacles in seeking care is crucial.